Religious and spiritual journeys of LGBT older adults in rural Southern Appalachia - Dakin, Emily (Journal of religion, spirituality & aging, 2022)
This article reports on religious and spiritual experiences of 11 lesbian, gay, bisexual, and/or trans*-identified (LGBT) older adults in rural southern Appalachia. Template analysis of interview data yielded themes including: harmful experiences with Christianity in childhood and adulthood, religion and spirituality as sources of support, current participation in supportive Christian churches, and personalized approaches to spirituality and religion. Despite prior harmful experiences in some cases, religion and spirituality now provided meaning, strength, and support for most of the participants. The article concludes with implications for theory, research, and professional practice for clergy, social workers and other helping professionals.